HUBUNGAN DUKUNGAN KELUARGA DENGAN MOTIVASI PASIEN GAGAL GINJAL KRONIK DALAM MENJALANI HEMODIALISA - Rilla, Eldessa Vava; Suindrayasa, I Made (Coping: Community of Publishing in Nursing; Vol 12 No 1 (2024): Februari 2024DO - 10.24843/coping.2024.v12.i01.p05, 2024)
Chronic kidney disease is a disease caused by the kidneys not functioning properly, because the kidneys are unable to maintain metabolism, fluid balance and electrolytes, causing uremia. Chronic kidney disease patients undergoing hemodialysis really need family support. Support from the patient's family will increase the patient's motivation in undergoing treatment. From the results of the preliminary study, there are still several patients undergoing hemodialysis therapy who do not receive support from their families. Family support and motivation play a very important role for patients suffering from chronic kidney disease who are undergoing hemodialysis. The aim of this research is to analyze the relationship between family support and the motivation of chronic kidney disease patients in undergoing hemodialysis at Dr. Slamet Garut Regional Hospital. This research uses a categorical descriptive method with a cross sectional approach. The sampling technique used was purposive sampling. The number of samples in this study was 60 respondents. The bivariate analysis used was chi square. The results of this study prove that there is a relationship between family support and the motivation of chronic kidney disease patients to undergo hemodialysis at RSUD dr. Slamet Garut with p-value (0,001). The conclusion of this study shows that there is a significant relationship between family support and the motivation of chronic kidney disease patients undergoing hemodialysis at RSUD dr. Slamet Garut.